Model EPQ Multi Item yang Dimodifikasi untuk Dua Permintaan secara Simultan - Taufiq Rahman; Jonrinaldi Jonrinaldi; Henmaidi (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2017)
Inventory is one of many factors of the business operation that need to be controlled by industries in order to improve efficiency, enhance productivity, and decrease the holding cost. The holding cost of inventories in supply chain contribute to 20% - 40% of the product value. It can be controlled by applying appropriate inventory model, such as EPQ/Economic Production Quantity and EOQ/Economic Order Quantity. EPQ is an inventory model that used to determine the optimum production lot size with balanced the production setup cost and holding cost. Even the classic EPQ has applied widely in industries, the assumption used by this model differed between the researchers whether it is continuous or discrete demand, because the multi delivery or discrete demand is mostly used by industries. Even so, there are industries that used both continuous and discrete demand simultaneously. Based on previous research, there was an advanced EPQ model that synchronizing both assumptions simultaneously, but it still addressed single item problem. Since almost the industries produced multi item, this model has lack of applicability. Therefore, this research proposed a multi item EPQ Model that synchronizing continuous and discrete demand simultaneously. The solution procedure that used in this proposed model are classical calculus method/differential calculus and simultaneous approach. A numerical example is given to show the effectiveness of the proposed approach based on the data from the literature.